Analysis of Gender Stereotypes in Tanzania ' s Television Commercial Advertisements - Kahamba, Judith S; Sife, Alfred S. (University of Dar es Salaam Library Journal, 2018)
This study analysed gender stereotypes in Tanzania ' s television commercial advertisements. In all, 71 advertisements were recorded from nine television channels €”TBC1, ITV, Azam One, Azam Two, Sinema Zetu, Channel 10, Clouds TV, Star TV and East Africa TV. The units of analysis were television commercials that contained at least one adult female or male character. The recorded advertisements were then subjected to content analysis. Quantitative data was analysed with the help of SPSS. The study findings indicate that there was an equal distribution of male and female characters in television adverts and that the majority of central figures were aged between 18 and 35 years. A central figure in this study was an adult person playing a major role by virtue of either speaking or having an exposure on a screen. Women in television commercials were younger than their male counterparts, were portrayed mostly in home settings and as non-professionals, with their primary occupation being homemakers. Women were also primarily associated with the promotion of household products and they frequently appeared wearing non-formal attire. The findings also indicate that men dominated the ad voiceovers and that they often provided scientific arguments in television commercials. The findings of the study imply that, despite many efforts made to address gender inequalities in the country, Tanzania ' s televisions continue to perpetuate such inequalities through stereotypical portrayal of men and women. Thus more efforts are necessary to make the media broadcast gender-sensitive and gender-responsive content.